Production of polymer particles below 5 μm by wet grinding - Schmidt, Jochen; Plata Acevedo, Miguel Angel; Tröger, Sulay; Peukert, Wolfgang (Powder Technology, 2012)
Polymeric microparticles that may be used in rapid prototyping processes typically are produced by either polymerization processes or cryogenic grinding in impact mills at liquid nitrogen temperature (− 196 °C) or by dry grinding at solid carbon dioxide temperature (− 78 °C). Within this account an alternative approach for the production of polymer particles is presented. It is shown that wet grinding of polymers in a stirred media mill and organic solvents (ethanol, hexane) at reduced temperatures down to − 80 °C is a suitable method to produce polymer particles of mean diameter smaller than 5 μm with narrow particle size distribution. Results are presented for wet grinding of polystyrene (PS) and polyetheretherketone (PEEK). The influence of the mechanical properties of the polymers under consideration and the influence of the process parameters, namely stress energy, process time and especially temperature and solvent viscosity are addressed. Remarkably, we found in case of PEEK that the mean diameter is one order of magnitude smaller than the zone of plastic deformation estimated from fracture toughness and yield stres
Keywords: Wet grinding; Micro-grinding; Stirred media mill; Polymer; Polystyrene; PEEK